2021
DOI: 10.1002/ps.6578
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate‐induced resistance to Delia platura (Diptera: Anthomyiidae) in Lupinus mutabilis

Abstract: BACKGROUND: Andean lupin (Lupinus mutabilis Sweet) is an important leguminous crop from South America with a high protein content. In Ecuador, lupin yields are severely affected by the infestation of Delia platura larvae on germinating seeds. The application of elicitor molecules with activity against herbivorous insects to control D. platura infestation constitutes an unexplored and promising alternative for chemical insecticides. In this study, methyl jasmonate (MeJA), hexanoic acid, menadione sodium bisulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 141 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…After the MeJA pretreatment of the seeds of Lupinus mutabilis Sweet, only the seeds treated with MeJA showed the ability to damage insects. It was also revealed that the use of MeJA upregulated the activities of the JA biosynthesis genes LmLOX2 and LmAOS , as well as those of jasmonic acid-related defense genes ( LmTPS1 , LmTPS4 , LmPI2 , LmMBL , LmL/ODC , LmCSD1 , and LmPOD ) [ 79 ]. These results suggest that MeJA, as an inducer, may induce the defense mechanism of plants against pathogens and insects by regulating the biosynthesis of terpenoids, protease inhibitors, and antioxidant enzyme activities.…”
Section: The Role Of Ja In Vegetable Crop Resistancementioning
confidence: 99%
“…After the MeJA pretreatment of the seeds of Lupinus mutabilis Sweet, only the seeds treated with MeJA showed the ability to damage insects. It was also revealed that the use of MeJA upregulated the activities of the JA biosynthesis genes LmLOX2 and LmAOS , as well as those of jasmonic acid-related defense genes ( LmTPS1 , LmTPS4 , LmPI2 , LmMBL , LmL/ODC , LmCSD1 , and LmPOD ) [ 79 ]. These results suggest that MeJA, as an inducer, may induce the defense mechanism of plants against pathogens and insects by regulating the biosynthesis of terpenoids, protease inhibitors, and antioxidant enzyme activities.…”
Section: The Role Of Ja In Vegetable Crop Resistancementioning
confidence: 99%
“…All types of elicitors act as a signal, which is perceived by an elicitor-specific receptor from the cell membrane. After perception is initiated, a transduction cascade occurs, which conducts expression level change of various regulatory transcription factors/genes, resulting in increased synthesis and accumulation of secondary metabolites [41,42]. Studies concerning the comparisons of metabolite compositions of both embryo types are scarce.…”
Section: Somatic Embryogenesis and Secondary Metabolitesmentioning
confidence: 99%
“…Traditionally in South America, many indigenous communities have used medicinal plants as palliative treatment for certain illnesses and all this knowledge has been passed through generations (Table 1) [42]. According to IUCN, after a screening of the literature concerning endemic medicinal trees, 3 of them are endangered, 8 are vulnerable, 10 are not threatened, and 27 are least concerned.…”
Section: Tree Species With Medicinal Properties In South Americamentioning
confidence: 99%
“…The seedcorn maggot, Delia platura (Meigen) (Diptera: Anthomyiidae), is currently recognised as an agricultural pest with a near-cosmopolitan range and a high diversity of larval hosts, both living and dead (Griffiths 1993). Being highly polyphagous, the larvae of D. platura will feed on many species of cultivated vegetables and field crops, with infestations that can reach nearly 100% of sampled plants, depending on the crop (Hough-Goldstein and Hess 1984; Griffiths 1993; Howard et al 1994; Soroka and Dosdall 2011; Guerra et al 2017; Erazo-Garcia et al 2021). The species can act as a primary or secondary invader of host plants and can even complete its development in decaying organic matter (Finch 1989).…”
Section: Introductionmentioning
confidence: 99%